The Greater Metropolitan Medical Alumni Council (GMMAC): The Realization of a Need. (1st August 2013) - Belilos, Elise; Oleske, James M.; Medow, Norman B.; Sadovsky, Richard; Campese, Christopher L.; Bello, Jacqueline A.; Swan, Kenneth G.
Abstract : Objective: The greater New York metropolitan area includes 8 medical schools. Their alumni association (AA) presidents formed a council 6 years ago, meeting 3 times a year to share ideas and identify best practices to solve mutual problems challenging students and alumni. Methods: A survey of the 8 medical AAs was conducted; all responded, and the results constitute the data in this report. Results: Mean AA membership was 2509 or 33% of mean alumni populations (7489). Two AAs conferred membership at graduation; hence, 100% of alumni were AA members. Omitting these 2 AAs reduced mean participation to 1722 or 23%. Alumni association support staff averaged 3.8 persons (range, 1–7 persons). The 2 most frequently cited AA challenges were membership and fund-raising. All AAs had annual or biennial reunions and considered the reunion to be a major commitment of resources. Despite this commitment, mean reunion attendance was only 242 alumni (range, 40–500 alumni) or 7.3% of alumni in anniversary years (5-year intervals). The mean number of alumni who contributed annually to their alma mater through its AA was 1936 alumni (range, 500–3500 alumni), or 26% (range, 5%–47%). Medical AAs reported mean assets of 2, 755, 000 (range, 6475–11, 000, 000). The mean AA budget was 298, 750, of which 65% (range, 13%–100%) was devoted to "medical student support". The most frequently cited student activities were "career night" (100%), "white coat ceremonies" (63%), medical equipment (stethoscopes, etc, 50%), and alumni host programs (38%). Eleven additional medical student activities received financial support from the 8 AAs in varying proportions. Conclusions: Each AA in the Greater Metropolitan Medical Alumni Council has derived significant benefit from the application of best practices to its individual problem set. In particular, a nascent AA developed significant momentum in its formation and development by its participation in the Greater Metropolitan Medical Alumni Council. Additionally, these data provide a foundation for the development of best practices within medical school AA for optimizing support of student programs and alumni participation. Stronger AAs will translate into enhanced support of educational programs for medical students. We urge formation of similar medical AA organizations in other metropolitan areas.